The treatment of mild upper respiratory tract infections - a position paper with recommendations for best practice - Andrew Smith; Peter Kardos; Oliver Pfaar; Winfried Randerath; Guillermo Estrada Riolobos; Fulvio Braido; Laura Sadofsky (BioExcel Publishing Ltd, 2023)
Following the waning severity of COVID-19 due to vaccination and the development of immunity, the current variants of SARS-CoV-2 often lead to mild upper respiratory tract infections (MURTIs), suggesting it is an appropriate time to review the pathogenesis and treatment of such illnesses. The present article reviews the diverse causes of MURTIs and the mechanisms leading to symptomatic illness. Different symptoms of MURTIs develop in a staggered manner and require targeted symptomatic treatment. A wide variety of remedies for home treatment is available, including over-the-counter drugs and plant-derived substances. Recent pharmacological research has increased the understanding of molecular effects, and clinical studies have shown the efficacy of certain herbal remedies. However, the use of subjective endpoints in these clinical studies may suggest limited validity of the results. In this position paper, the importance of patient-centric outcomes, including a subjective perception of improved well-being, is emphasized. A best practice approach for the management of MURTIs, in which pharmacists and physicians create an improved multi-professional healthcare setting and provide healthcare education to patients, is proposed. Pharmacists act as first-line consultants and provide patients with remedies, considering the individual patient's preferences towards chemical or plant-derived drugs and providing advice for self-monitoring. Physicians act as second-line consultants if symptoms worsen and subsequently initiate appropriate therapies. In conclusion, general awareness of MURTIs should be increased amongst medical professionals and patients, thus improving their management.